2010
DOI: 10.1007/s11999-010-1399-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Subsequent Revision after Primary and Revision Total Joint Arthroplasty

Abstract: Background Revision is technically more demanding than primary total joint arthroplasty (TJA) and requires more extensive use of resources. Understanding the relative risk of rerevision and risk factors can help identify patients at high risk who may require closer postsurgical care. Objectives/purposes We therefore evaluated the risk of subsequent revision after primary and revision TJA in the elderly (65 years or older) patient population and identified corresponding patient risk factors. Patients and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
158
3
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 249 publications
(187 citation statements)
references
References 24 publications
18
158
3
8
Order By: Relevance
“…The proportion of patients with older age (C 65 years) undergoing revision THA affects the underlying frequencies of population comorbidities. Revision THAs tend to be performed in sicker patients, and comorbidities particularly influence the rate of revision after primary THA [38], including the rate of early revision in the elderly [9]. Risk-assessment tools may offer physicians the opportunity to counsel elderly patients regarding the specific risks of infection after THA [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of patients with older age (C 65 years) undergoing revision THA affects the underlying frequencies of population comorbidities. Revision THAs tend to be performed in sicker patients, and comorbidities particularly influence the rate of revision after primary THA [38], including the rate of early revision in the elderly [9]. Risk-assessment tools may offer physicians the opportunity to counsel elderly patients regarding the specific risks of infection after THA [10].…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the clinical success of THAs and TKAs, the number of revision THAs [4,38] and TKAs [4,21,34,35] performed in the United States has increased with time. The revision THA and TKA caseload per orthopaedic surgeon also has increased [28].…”
Section: Introductionmentioning
confidence: 99%
“…THA outcomes have previously been characterized at the population level for the Medicare population [3,16,17]. Most studies have shown that THA is associated with high rates of success as defined by decreased pain and improved function in patients who suffer from disabling arthritis of the hip [12].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have attempted to summarize the causes and epidemiology of revision procedures [5,6,39] and what can be done to minimize clinical and radiographic failures [34,35]. One aspect where surgeons and patients may differ, however, lies in the difference between a patient's and surgeon's definition of a successful procedure.…”
Section: Introductionmentioning
confidence: 99%